Impacts of Circadian Gene Period2 Knockout on Intestinal Metabolism and Hepatic Antioxidant and Inflammation State in Mice. (19th July 2022) - Zhen, Yongkang; Xi, Zanna; Hu, Liangyu; Chen, Yifei; Ge, Ling; Wei, Wenjun; Loor, Juan J.; Yang, Qingyong; Wang, Mengzhi
Abstract : The period circadian regulator 2 ( Per2 ) gene is important for the modulations of rhythmic homeostasis in the gut and liver; disruption will cause metabolic diseases, such as obesity, diabetes, and fatty liver. Herein, we investigated the alterations in intestinal metabolic and hepatic functions in Per2 knockout ( Per2 -/-, KO) and wild-type ( Per2 +/+, WT) mice. Growth indices, intestinal metabolomics, hepatic circadian rhythms, lipid metabolism, inflammation-related genes, antioxidant capacity, and transcriptome sequencing were performed after euthanasia. Data indicated that KO decreased the intestinal concentrations of amino acids such as γ -aminobutyric acid, aspartic acid, glycine, L-allothreonine, methionine, proline, serine, and valine while it increased the concentrations of carbohydrates such as cellobiose, D-talose, fucose, lyxose, and xylose compared with WT. Moreover, the imbalance of intestinal metabolism further seemed to induce liver dysfunction. Data indicated that Per2 knockout altered the expression of hepatic circadian rhythm genes, such as Clock, Bmal1, Per1, Per3, Cry1, and Cry2 . KO also induced hepatic lipid metabolism, because of the increase of liver index and serum concentrations of low-density lipoprotein, and the upregulated expression of Pparα, Cyp7a1, and Cpt1 . In addition, KO improved hepatic antioxidant capacity due to the increase activities of SOD and GSH-Px and the decrease in concentrations of MDA. Lastly, KO increased the relative expression levels of hepatic inflammation-related genes, such as Il-1β, Il-6, Tnf-α, Myd88, and Nf-κB p65, which may potentially lead to hepatic inflammation. Overall, Per2 knockout induces gut metabolic dysregulation and may potentially trigger alterations in hepatic antioxidant and inflammation responses.